‘It just be like that’: young men’s and women’s attributions of negative sexual behavior - Mullins, Christopher W. (Journal of criminal psychology, 2017)
This paper provides an examination of the role that male peer support plays in negative sexual attitudes and behaviors vis-àvis women. Drawing on semi-structured interview data collected from at risk high school students in an urban Midwestern town, we are able to qualitatively explore attitudes, behaviors, and experiences within this group of young men and women as they relate to negative sexual behaviors. We integrate routine activites theory with a male peer support theory of violence to to obtain a more holistic view of negative sexual behaviors. Male peer support models provide us with a theoretical explanation of the variation within motivation, thereby filling a serious gap in the routine activities perspective.